2006
DOI: 10.1159/000096715
|View full text |Cite
|
Sign up to set email alerts
|

Parapharyngeal Abscess: Comprehensive Management Protocol

Abstract: Parapharyngeal infections are rare, but they cause serious morbidity and mortality. Therefore, until now, the recommended treatment of parapharyngeal abscess has been early open surgical drainage. The purpose of this study is to review the clinical course and outcome of treatment in parapharyngeal abscess according to method of treatment. A prospective study was designed for parapharyngeal abscess in patients admitted for deep neck infection. During an 8-year period, from June 1994 to January 2003, 34 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 34 publications
3
34
0
2
Order By: Relevance
“…Securing the airways with tracheostomy or intubation is also necessary when upper airway obstruction occurs, as it is the most likely cause of fatality in this patient group [18]. While the therapeutic application of needle aspiration has been used in patients with no difference in complication rates [19], early open surgical drainage remains the definitive treatment for deep neck abscesses. If the size of the abscess is small and there are no imminent complications, a trial of conservative management may be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Securing the airways with tracheostomy or intubation is also necessary when upper airway obstruction occurs, as it is the most likely cause of fatality in this patient group [18]. While the therapeutic application of needle aspiration has been used in patients with no difference in complication rates [19], early open surgical drainage remains the definitive treatment for deep neck abscesses. If the size of the abscess is small and there are no imminent complications, a trial of conservative management may be attempted.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, parapharyngeal abscesses were approached via transcervical incision, but more recent studies have shown that transoral approaches are safe and effective with abscesses limited to the parapharyngeal space and not spreading into other deep neck spaces, or lateral to the great vessels [2,12,13]. Oh and coworkers recommend that all patients undergo a preoperative CT scan to accurately localize the abscess and prevent injuring the neurovascular structures in the posterior compartment of the parapharyngeal space [12].…”
Section: Discussionmentioning
confidence: 99%
“…9 A number of authors have suggested using surgery only when patients do not respond to medical treatment. 8,9 Conclusion: In summary, deep neck abscess may be missed in an atypical or subclinical presentation and require a high index of suspicion. Therefore, in case of acquired torticollis with low grade fever and normal oropharyngeal findings, the diagnosis of deep space neck infection such as RPA must be ruled out.…”
Section: Case Reportmentioning
confidence: 99%
“…Measurement greater than 7mm at 2 nd cervical vertebra and 22mm (in adult) and 14mm (in children) at 6 th cervical vertebra are considered abnormal and strongly support the diagnosis of RPA. 8 Most of the time, a good lateral neck X-ray is enough to establish diagnosis but CT scan is superior as it can be used to evaluate the extension of an abscess thus helping in determining treatment regimen. Medical records of 24 children with RPA were reviewed and it is reported that CT scan had a 75% accuracy for correctly identifying the abscess.…”
Section: Case Reportmentioning
confidence: 99%